Spirophenylacridine‐2, 7‐(diphenylphosphineoxide)‐fluorene: A Bipolar Host for High‐Efficiency Single‐Layer Blue Phosphorescent Organic Light‐Emitting Diodes. Issue 2 (4th November 2019) - Lucas, Fabien; Ibraikulov, Olzhas A.; Quinton, Cassandre; Sicard, Lambert; Heiser, Thomas; Tondelier, Denis; Geffroy, Bernard; Leclerc, Nicolas; Rault‐Berthelot, Joëlle; Poriel, Cyril
Abstract: Herein, a high‐efficiency host material for single‐layer phosphorescent organic light‐emitting diodes (SL‐PhOLEDs) is reported. This host material is synthesized via an efficient approach and is constructed on the association of an electron‐rich phenylacridine unit connected by a spiro carbon atom to an electron‐deficient 2, 7‐bis(diphenylphosphineoxide)‐fluorene. In addition to a high E T value and adequate highest occupied molecular orbital/lowest unoccupied molecular orbital energy levels, the key point in this molecular design is the suitable balance between hole and electron mobilities, which leads to a high‐performance blue SL‐PhOLED with an external quantum efficiency of 17.6% (current efficiency = 37.8 cd A −1 and power efficiency = 37.1 lm W −1 ) and a low V on of 2.5 V. This performance shows that the molecular design of the present host fulfills the criteria required for high‐efficiency SL‐PhOLEDs. The present performance is one of the highest reported to date for blue SL‐PhOLEDs and more importantly shows the potential of such a molecular design to reach very high‐performance single‐layer devices. Abstract : A very high‐efficiency host material for blue single‐layer phosphorescent organic light‐emitting diode (OLED) (external quantum efficiency reaching 17.6%) is reported. This host is synthesized via an efficient approach, displays a high E T, adequate highest occupied molecular orbital/lowest unoccupied molecular orbital energy levels, and suitable balance between hole and electron mobilities displaying all the required properties for reaching high‐performance single‐layer phosphorescent OLED.